3(4x-4)-4=11-(4x-5)

Simple and best practice solution for 3(4x-4)-4=11-(4x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x-4)-4=11-(4x-5) equation:



3(4x-4)-4=11-(4x-5)
We move all terms to the left:
3(4x-4)-4-(11-(4x-5))=0
We multiply parentheses
12x-(11-(4x-5))-12-4=0
We calculate terms in parentheses: -(11-(4x-5)), so:
11-(4x-5)
determiningTheFunctionDomain -(4x-5)+11
We get rid of parentheses
-4x+5+11
We add all the numbers together, and all the variables
-4x+16
Back to the equation:
-(-4x+16)
We add all the numbers together, and all the variables
12x-(-4x+16)-16=0
We get rid of parentheses
12x+4x-16-16=0
We add all the numbers together, and all the variables
16x-32=0
We move all terms containing x to the left, all other terms to the right
16x=32
x=32/16
x=2

See similar equations:

| 2x-24=-x^2 | | 0=x=180 | | A(t)=10000(1.02)^(20) | | y-2.6=4.5 | | 20x+32=16x | | (1/2)^n=1/8 | | 12x=80-20x | | 5x^2=-10x-4 | | 2(2x+4)=6x+5-2x+3 | | f(1)-f(0)=2020 | | 72-8t=0 | | 72-8t=32 | | 5c+8=2c-4 | | 2x4-6x2-8=0 | | 13=3+25t-5{t}^{2} | | H=-16t2+62t+2 | | 8y-8y=6-6 | | m-0,4=2.33 | | 2(3y+2.8)=8.6 | | 7x+10=8x-12 | | 4x-4=3x-35 | | 18x^2+60x+16=0 | | X+3y=26.X-3y=-22 | | X+2x+(2x+1,6)=28,60 | | 2(3x-5)=x2-4 | | 6=3x-24 | | x*(15/100)=12000 | | 8x–3=5x+21 | | 440=n/1(4+2n) | | 5(9k+2)+8(3=4k) | | -26=4+y/5 | | 5=3u-7 |

Equations solver categories